TJNPR 2018
DOI: 10.26538/tjnpr/v2i5.5
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal Assessment of Fractions of Aristolochia albida Rhizome on Culex quinquefasciatus

Abstract: Aristolochia albida is a plant, native of Africa that has found various applications including antiparasite and anti-snake venom. In the present study, Aristolochia albida rhizome was extracted successively with chloroform and methanol by maceration technique. The extracts were tested for their larvicidal activity against 3 rd and 4 th instar larvae of Culex quinquefasciatus mosquito, according to WHO guidelines for larvicidal bioassay, with slight modifications. Fractionation of the chloroform extract was car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The research revealed that the extracts of SG and BA leaves contain vast array of phytochemicals, namely flavonoids, steroids, triterpenes, cardiac glycosides, tannins, saponins and alkaloids. This is supported by previous studies on evaluation of phytoconstituents of plant extracts (Usman et al, 2018;Hassan et al 2020;Nazneen et al, 2016). These phytochemicals have been reported to exhibit potency in some physiological imbalance; for example, flavonoids play a role as antioxidant agents (Savithramma et al, 2011); alkaloids are important in antimicrobial, analgesic, and other antispasmodic actions (Savithramma et al, 2011;Chatoui et al, 2016;El Hattabi et al, 2016) also steroids have been found to possess anti-inflammatory potency (Chatoui et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…The research revealed that the extracts of SG and BA leaves contain vast array of phytochemicals, namely flavonoids, steroids, triterpenes, cardiac glycosides, tannins, saponins and alkaloids. This is supported by previous studies on evaluation of phytoconstituents of plant extracts (Usman et al, 2018;Hassan et al 2020;Nazneen et al, 2016). These phytochemicals have been reported to exhibit potency in some physiological imbalance; for example, flavonoids play a role as antioxidant agents (Savithramma et al, 2011); alkaloids are important in antimicrobial, analgesic, and other antispasmodic actions (Savithramma et al, 2011;Chatoui et al, 2016;El Hattabi et al, 2016) also steroids have been found to possess anti-inflammatory potency (Chatoui et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…All larvae were starved 24 hours before bio-larvicidal activity testing and cytotoxicity. [27][28][29] Bio-larvicidal activity Varying concentrations of the extract were prepared according to the description of . 30 A modified version of the WHO protocol for larvicidal bioassays was utilized in this study.…”
Section: Mosquito Colonization and Maintenancementioning
confidence: 99%
“…[17][18][19][20][21] The use of Streptomyces secondary metabolites has not gone beyond the lab, researchers have discovered the presence of chitinase producing Streptomyces strains from soil with evidence of secondary metabolite production and bioactive traits. [19][20][21][22][23][24][25][26][27] A previous study 28 revealed the presence of high antimicrobial and bio-larvicidal activity of Streptomyces isolate GA9 from soil sample against clinically significant test organisms and Anopheles larvae. Despite this novel finding from the pioneering study on the use of Streptomyces secondary metabolite as alternative to synthetic pesticides, there are © 2024 the authors.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of traditional uses for species of the genus Aristolochia were found in the literature. Of the traditional uses cited, the most common uses are anticancer (33 articles) , antibacterial (31 articles) [23,25,29,30,38,39,45,49,, antioxidants (18 articles) [22,25,29,33,34,46,55,60,61,70,73,74,[77][78][79][80][81][82], snake anti-venom (13 articles) [21,22,39,40,76,[83][84][85][86][87][88][89][90], anti-inflammatory (11 articles) [22,40,46,47,74,86,[91][92][93][94]…”
Section: Ethnomedicinal Usementioning
confidence: 99%